Perception of soya and rice farmers about occupational risks (Research, Society and Development, 2020)
Objective: to know the perception of soybean and rice farmers about occupational risks. Methodology: descriptive and exploratory study, with a quantitative approach. The scenario was a rural environment in the extreme south of Brazil. Participated 241 soybean and rice farmers. Data were collected through a semi-structured questionnaire, from july to november 2018. Pearson's chi-square or Fisher's exact tests were used. To control confounding factors, Poisson regression analysis was applied. Results: the perception of self-reported occupational risks was 97.2%. The following stand out: physical, chemical, ergonomic and biological risks. They maintained statistical significance to the perception of occupational biological and ergonomic risks. Conclusion: these findings are believed to be guiding instruments for health-promoting and disease-prevention actions by the research group in partnership with primary health care, aimed at reducing occupational risks in the workplace.